Polycentric urban development in post-socialist context: the case of the Budapest Metropolitan Region - Tünde Szabó (Hungarian Geographical Bulletin, 2014)
Even though the concept of polycentric urban development has been high on the agenda in the literature it has rarely come to the fore in academic papers dealing with the postsocialist cities. The main aim of this paper is to analyse the evolving polycentric pattern of urban development in the metropolitan region of Budapest. For the purpose of study we use commuting data of the 1990, 2001 and 2011 national census. The rapid transformation of Budapest after 1989 the re-establishment of market mechanisms, the privatisation of housing, the liberalisation of the property market, and the growing re-integration of the city to the world economy aff ected not only the core city but also the metropolitan periphery. The previously rather homogeneous structure of the metropolitan periphery experienced significant changes in the course of the transformation. The advantages of location, which had been insignificant during the state-socialist period, once again became truly beneficial which resulted in growing disparities in the metropolitan periphery. Since 1990 the functional interplay, cooperation, interdependence as well as physical infrastructural linkages between Budapest and its metropolitan zone have been further intensified. Residential suburbanisation and the suburbanisation of business activities led to new flows of commuting within the metropolitan region. Our findings show that the reallocation of urban functions took place in the wider metropolitan zone of Budapest among existing centres, which fits to the European version of post-suburbanisation concept rather than the US one.